1995
DOI: 10.1017/s0020818300033373
|View full text |Cite
|
Sign up to set email alerts
|

From domestic to international justice: the welfare state and foreign aid

Abstract: Foreign aid often is interpreted as an international projection of domestic income redistribution mechanisms, and many authors suggest that differences between welfare states account for variations in donor behavior. A new understanding of the welfare state can improve traditional explanations of this linkage. Existing studies of the welfare–aid relationship use two welfare state indicators: domestic spending and partisan politics. We propose a third type of indicator—the institutional attributes of the welfar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
89
1
2

Year Published

1998
1998
2019
2019

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 169 publications
(97 citation statements)
references
References 63 publications
3
89
1
2
Order By: Relevance
“…The rhetoric of the left about aid typically evokes social justice, solidarity and public commitments, whereas discourses on the right refer instead to dependency, inefficiency, and waste. In countries where social-democratic parties have been powerful and where they have built a generous and universal welfare state, foreign aid tends to be at a high level (Noël and Thérien 1995;Thérien and Noël 2000). Where conservatives have dominated, domestic inequalities remain more important and they tend to prevail in the public's mind, over international development issues ( The relationship between ideological/partisan orientations and support for foreign aid, however, has rarely been tested rigorously.…”
Section: Two Publics?mentioning
confidence: 99%
“…The rhetoric of the left about aid typically evokes social justice, solidarity and public commitments, whereas discourses on the right refer instead to dependency, inefficiency, and waste. In countries where social-democratic parties have been powerful and where they have built a generous and universal welfare state, foreign aid tends to be at a high level (Noël and Thérien 1995;Thérien and Noël 2000). Where conservatives have dominated, domestic inequalities remain more important and they tend to prevail in the public's mind, over international development issues ( The relationship between ideological/partisan orientations and support for foreign aid, however, has rarely been tested rigorously.…”
Section: Two Publics?mentioning
confidence: 99%
“…Combined with what is already known about parties, the welfare state and foreign aid, these three propositions yield two hypotheses: In the first hypothesis, the logic at work is the following: when they hold power for a long period, parties of the left tend to institutionalize social-democratic welfare state principles and practices, which are themselves the best predictors of a country's foreign aid effort. The second hypothesis derives from the observation that Christian-democratic cumulative power favors high levels of social spending, and that a country's social spending is strongly associated with its foreign aid (Huber, Ragin and Stephens 1993;Noël and Thérien 1995).…”
Section: Theoretical Modelmentioning
confidence: 99%
“…It flows from the idea that mass publics are influenced by their country's political and social institutions, but also 11 acknowledge the impact of policy results, at home and abroad. Previous studies have suggested that principles institutionalized through social policies shape what political actors "consider to be morally defensible behavior" (Rothstein, 1998, p. 138; see also Noël & Thérien, 1995). This implies that the public should value equality more strongly and be more sensitive to international redistribution in countries with a social-democratic tradition.…”
mentioning
confidence: 99%
“…The comparative literature on the welfare state and development assistance suggests that there is a link between a country's domestic and foreign commitments to redistribute (Pratt, 1989;Stokke, 1989a;Lumsdaine, 1993;Noël & Thérien, 1995). Logically, this link should also be visible in public opinion.…”
mentioning
confidence: 99%